Thermal Emission and Confirmation of the Frigid White Dwarf Exoplanet WD 1856+534 b - Mary Anne Limbach; Andrew Vanderburg; Ryan J. MacDonald; Kevin B. Stevenson; Sydney Jenkins; Simon Blouin; Emily Rauscher; Rachel Bowens-Rubin; Elena Gallo; James Mang; Caroline V. Morley; David K. Sing; et al. (The Astrophysical Journal Letters)
We report the detection of thermal emission from and confirm the planetary nature of WD 1856+534 b, the first transiting planet known to orbit a white dwarf (WD) star. Observations with JWST’s Mid-Infrared Instrument reveal excess mid-infrared emission from the WD, consistent with a closely orbiting Jupiter-sized planet with a temperature of $18{6}_{-7}^{+6}$ K. We attribute this excess flux to the known giant planet in the system, making it the coldest exoplanet from which light has ever been directly observed. These measurements constrain the planet’s mass to no more than six times that of Jupiter, confirming its planetary nature and ruling out previously unexcluded low-mass brown dwarf scenarios. WD 1856+534 b is now the first intact exoplanet confirmed within a WD’s “forbidden zone,” a region where planets would have been engulfed during the star’s red giant phase. Its presence provides direct evidence that planetary migration into close orbits—including the habitable zone—around WDs is possible. With an age nearly twice that of the solar system and a temperature akin to our own gas giants, WD 1856+534 b demonstrates JWST’s unprecedented ability to detect and characterize cold, mature exoplanets, opening new possibilities for imaging and characterizing these worlds in the solar neighborhood.